Case Study: Using 3D Speckle Tracking Echocardiography for Left Ventricular Aneurysm Diagnosis - O. A. Mazur; L. M. Hrubyak; O. V. Kupchynskyi; N. V. Bankovska (Ukrainian Journal of Cardiovascular Surgery, 2020)
Nowadays magnetic resonance imaging (MRI) is a gold standard for diagnosing abnormalities of left ventricular geometry and function, however, it is not universally accessible. Furthermore, MRI is not compatible with pacemakers and similar devices. 3D speckle tracking echocardiography (3D STE) is a cutting-edge echocardiography imaging technique for myocardial deformation assessment. As such, 3D STE looks very promising for diagnosing structural complications of myocardial infarction (MI) and choosing the optimal surgical techniques.In this case study, we used 3D STE to assess left ventricular function in a patient with left ventricular aneurysm.The patient was admitted to National Amosov Institute of Cardiovascular Surgery three weeks after having a second MI (the first MI was reported 4 years ago). His coronary angiography showed diffuse coronary artery disease. 2D echocardiography (performed on Toshiba Artida) results: end-diastolic volume (EDV) 206 ml, end-systolic volume (ESV) 141 ml, ejection fraction (EF) (Simpson’s method) 31%. An object sized 2.2*1.6 cm was discovered in the apical region (left ventricular thrombus). 3D STE results: EDV 209 ml, ESV 182 ml, EF 13%. Global area strain (GAS) was considerably decreased (–13.7 %) showing the pattern of ischemic cardiomyopathy with multivessel disease. Due to several reasons, it was impossible to obtain an MRI scan, so a CT coronary angiography was performed (Toshiba Aquilion One). The results of multi-slice computed tomography (MSCT) were consistent with those of echocardiography.According to the results, the initial plan to resect the apical akinesia region was ruled out. The patient underwent coronary artery bypass grafting (CABG) (4 shunts), the removal of thrombi from the left ventricle (additional fresh thrombi were discovered during the surgical intervention), and left ventricular aneurysm repair under cardiopulmonary bypass. Post-treatment 3D STE results: EDV dropped to 135 ml, EF rose from 13% to 32%. GAS increased up to –20.4 %, while the strains of all segments increased to subnormal levels. The overall dynamics was positive, and the patient was discharged to undergo postoperative rehabilitation.The case shows that 3D STE data is consistent with CT data in patients with abnormal ventricular remodeling. 3D STE is a good method for differentiation between akinetic scar tissue and a dyskinetic left ventricular aneurysm.